«Сестра із сестрою, як риба з водою»: індивідуально-психологічні особливості та стосунки жінок-сиблінгів в залежності від умов зростання в сім’ї. - Луценко, Олена Львівна; Успенська, В.В. (Харків : ХНУ імені В.Н. Каразіна, 2021)
Стосунки та індивидуально-психологічні особливості сиблінгів є однією з найменш досліджених областей сімейної психології. Метою даного дослідження було визначення особливостей міжособистісних стосунків сестер, зв’язку цих стосунків з порядком народження сестер, іншими вірогідними сімейними чинниками та здатністю сестер до кокетства. Були використані метод семантичного диференціала Ч. Осгуда (СДФ) виявлення ставлення до себе та до сестри; розроблена авторами анкета чинників зростання у сім’ї та тест О.Л. Луценко, В.В. Волчанової для вимірювання здатності до кокетства. В результаті була підтверджена адаптивна та компенсаторна роль жіночого кокетства для підвищення матеріального становища жінки. Жінки цінують навчання кокетству – сестра сестру оцінює вище, якщо та її навчає кокетству. Вищій рівень власного кокетства пов’язаний із сприйняттям себе як сильної жінки, тобто як ресурс. Оцінка активності сестри виявилася включеною у різноманітні зв’язки з іншими сімейними чинниками, що свідчить про важливість даної характеристики у стосунках сиблінгів жіночої статі. За умови більшої різниці у віці сестри краще ставляться одна до одної, що було пояснено зменшенням конкуренції між ними. Старша сестра традиційно виконує у сім’ї більше функцій, через що вона може відчувати більше заздрості до сестри, ревнощі до матері, вважати себе більш активною. При цьому старші сестри краще ставляться до молодших, вище оцінюють їх, ніж їх молодші візаві.
"Sister with sister, like a fish with water": individual psychological characteristics and relationships of women-siblings depending on the growth conditions in their family.
Relationships and individual psychological features of siblings are one of the least studied areas of family psychology. The purpose of this study was to determine the characteristics of interpersonal relationships of sisters, the connection of these relationships with the order of sisters’ birth, other probable family factors and the ability of sisters to coquetry. Methods: 1) Osgood's method of semantic differential was used to identify attitudes towards oneself and one's sister; 2) the form of growth factors in the family developed by the authors, and 3) questionnaire of women’s adaptive potential in relationship with men (questionnaire of women coquetry) to measure the ability to coquetry of O.L. Lutsenko, V.V. Volchanova. The form collected data about age of women, education, social status, presence and number of children, marital status, presence of divorce in the parental family, religious affiliation and the degree of religion significance in life (open questions). Questions with a 5-point Likert scale were about: satisfaction with physical condition (health status), satisfaction with financial status, satisfaction with social relations, spiritual satisfaction, the degree of attachment to the sister, father, mother; degree of support from the father, mother; degree of competition with a sister in childhood - up to 18 years; the degree of envy (unfair luck) towards the sister; degree of loyalty to free discussion of sexual topics in the family; the degree of participation in the teaching of coquetry by the sister, mother, others. As a result, the adaptive and compensatory role of female coquetry to increase the financial position of women was confirmed. In conditions of low welfare, lack of parental support, the degree of coquetry increases. The mother also teaches her daughter more coquetry in the case of divorce. Women value learning to be coquettish: a sister rates her sister higher if she teaches her to be coquettish. The highest level of coquetry is associated with the perception of oneself as a strong woman, i.e. as a resource. The assessment of the sister’s activity was found to be included in various relationships with other family factors, which indicates the importance of this characteristic in the relationship of female siblings. When sisters have the greater age difference, they treat each other better, that was explained by the reduction of competition between them. The older sister traditionally performs more functions in the family, because of which she may feel more envious of her sister, jealous of her mother, and consider herself as more active. At the same time, older sisters treat younger ones better, evaluate them higher than their younger counterparts. Key words: siblings; sisters; individual psychological peculiarities; order of birth; age difference; coquetry
Keywords: сиблінги; сестри; індивідуально-психологічні особливості; порядок народження; різниця у віці; кокетство